SISTEM MANAJEMEN DALAM PENGELOLAAN BUMDES ARWANA DESA MAHATO - Abdul Wahid (Jurnal Ilmiah Cano Ekonomos, 2023)
BUMDes were born as a new approach in efforts to improve the village economy based on village needs and potential. BUMDES management is fully carried out by the village community. The BUMDes management system is by accepting community economic activities in an institutional form and business entity that is regulated in a professional manner, but still relying on the village's original capacity. The purpose of this study is the strategy for utilizing BUMDes business units and management systems in managing BUMDes Arwana Mahato Village to improve community welfare and supervision of BUMDes Arwana to improve employee performance. The approach used in this study is a qualitative-description. Data collection techniques used observation, interviews and documentation. While the informants in this study consisted of four people, namely the village head of Mahato Village, Director of BUMDes Arwana Mahato Village, Treasurer of BUMDes Arwana Mahato Village and the community. The data analysis techniques are data reduction, data collection, data presentation, data analysis and drawing conclusions. The results of the study show that first, the strategy for utilizing the BUMDes Arwana business unit is to increase community income through socialization, services in developing community businesses and savings and loans. Second, the management system in the management of BUMDes Arwana Mahato Village to improve community welfare through the planning, organizing, providing directions in the form of outreach and supervision by supervisors to oversee every BUMDes performance.